2000
DOI: 10.1097/00004424-200010000-00008
|View full text |Cite
|
Sign up to set email alerts
|

MRI Techniques in Early Stages of Cartilage Disease

Abstract: Cartilage degenerative diseases affect millions of people. Our understanding of these diseases and our ability to establish efficacious treatment strategies have been confounded by the difficulty of nondestructively evaluating the state of cartilage. Imaging strategies that allow visualization of cartilage integrity would revolutionize the field by allowing us to visualize early stages of degeneration and thus to evaluate predisposing factors for cartilage disease and changes resulting from interventions (eg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
150
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(151 citation statements)
references
References 130 publications
0
150
0
1
Order By: Relevance
“…Therefore, alternative methods for the estimation of the amounts of proteoglycans are desirable. The method of delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) (47,48) can be applied for this purpose. We found that the 23 Na residual quadrupolar interaction, which is conveniently measured by multiple quantum filtered NMR techniques, is sensitive to PG depletion (49,50).…”
Section: Na Spectroscopy and Imaging Of Intact And Pg-depleted Articumentioning
confidence: 99%
“…Therefore, alternative methods for the estimation of the amounts of proteoglycans are desirable. The method of delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) (47,48) can be applied for this purpose. We found that the 23 Na residual quadrupolar interaction, which is conveniently measured by multiple quantum filtered NMR techniques, is sensitive to PG depletion (49,50).…”
Section: Na Spectroscopy and Imaging Of Intact And Pg-depleted Articumentioning
confidence: 99%
“…There are many good reviews describing the basics and potential of MRI in cartilage assessment (1)(2)(3)(4)(5)(6)(7). This paper focuses on novel methodologies of highresolution MRI for the noninvasive characterization of cartilage network structure.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts are motivated by a compelling need to visualize cartilage features that are affected by disease or injury and that are expected to be modified by therapeutic strategies. Magnetic resonance imaging (MRI) approaches have emerged as the preferred means of imaging cartilage anatomy [ 10,13, 35,36], and numerous techniques are under development for the MRI assessment of cartilage biochemical properties [7,12,14,18,40,451.…”
Section: Introductionmentioning
confidence: 99%